Clinicopathological Spectrum of Cryoglobulinemic Glomerulonephritis without Evidence of Autoimmunity Disorders: A Retrospective Study from a Single Institute of China - Xin Zhang; Xiao-juan Yu; Chong-wen An; Zi-hao Yong; Su-xia Wang; Fu-de Zhou; Ming-hui Zhao (Karger Publishers, 2022)
Background: Cryoglobulinemic glomerulonephritis (Cryo-GN), caused by circulating cryoglobulins, has varied etiology and clinical-pathologic manifestations. This study aimed to investigate the clinicopathological spectrum and outcome of patients with various Cryo-GN in China. Methods: A retrospective review of 74 Chinese patients with biopsy-proven cryoglobulin-related renal lesions in Peking University First Hospital from 2010 to 2020 was performed. Results: The mean age at diagnosis was 52.9 ± 15.0 years, and the female-to-male ratio was about 2/5. For the etiology screening, serum/urine monoclonal immunoglobulin could be detected on immunofixation electrophoresis in 34% of patients, including 6 patients who had hematological malignancies. Fifty-seven percent of patients had HBV infection, far more than HCV infection (5%). Ten percent of patients had other infections, and 27% of patients were classified as essential or idiopathic. Eleven out of the 15 patients with type II cryoglobulinemia had a consistent monotype of serum monoclonal immunoglobulins and monoclonal cryoprecipitate. The clinical manifestations were similar between various types of cryoglobulinemia. Hematuria, proteinuria, hypertension, anemia, and chronic renal insufficiency were the most common features. Fifty-three percent of patients presented with nephrotic syndrome, and 32% experienced acute kidney injury. Hypocomplementemia, serum-positive rheumatoid factor activity, and skin lesions were reported in 45%, 29%, and 28% of patients, respectively. After a median of 24 months follow-up, 18 patients reached end-stage kidney disease. The clone-targeted treatment could retard the renal deterioration compared with immunosuppressive therapy. Conclusions: This was the largest single-center, clinicopathological retrospective study of Cryo-GN in China. Our data strongly support the association between monoclonal gammopathy and type II Cryo-GN. The renal responsive rate of immunosuppressant therapy is still suboptimal. The clone-targeted treatment shows promising effects in patients with type I or II Cryo-GN.